Promoting health and academic success : the whole school, whole community, whole child approach - Birch, David A.; Videto, Donna M. (Champaign : Human Kinetics, 2015)
This book provides direction for education and school health professionals interested in promoting student health and is valuable for individuals and groups interested in advocating for WSCC and for those engaged in the planning, implementation and evaluation of this new approach.
Part 1. Moving from coordinated school health to the whole school, whole community, whole child approach -- Part 2. Putting the focus on the child -- Part 3. Building partnerships and support -- Part 4. Planning, implementation, and evaluation -- Part 5. The path forward.
Includes bibliographical references and index.
1 2
Keywords: School health services -- United States; Health education -- United States; Health promotion -- United States; Health education; Health promotion; School health services; United States; School Health Services; Health Education; Health Promotion; United States